2023
DOI: 10.1108/amhid-08-2022-0027
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers experiences of caring for people with intellectual disability and dementia: a qualitative evidence synthesis

Abstract: Purpose A systematic review of the literature was completed to examine the needs of those who provide care to people with intellectual disability and dementia. The purpose of this paper was to develop an understanding of the complexities, challenges and support available to meet the needs of an ageing population. Design/methodology/approach A qualitative evidence synthesis was used to appraise 12 studies. An evidence synthesis approach was used to better understand the challenges caregivers experience in car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…It also highlights key factors that support carers within their caring role. Acton et al’s (2023) similar systematic review utilises only eight out of the fourteen studies included in this review, to map the challenges experienced by carers. Acton et al’s (2023) identified domains, such as gaps in knowledge and skills, burden and increased care demands are evidenced with the emerging themes of this review.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It also highlights key factors that support carers within their caring role. Acton et al’s (2023) similar systematic review utilises only eight out of the fourteen studies included in this review, to map the challenges experienced by carers. Acton et al’s (2023) identified domains, such as gaps in knowledge and skills, burden and increased care demands are evidenced with the emerging themes of this review.…”
Section: Discussionmentioning
confidence: 99%
“…These reviews fail to fully capture the experiences of the primary caregivers for people with a learning disability and dementia. A recent small-scale review has been published ( Acton et al, 2023 ) claiming to explore carers experience of caring for individuals with a learning disability and dementia. However upon review it would appear that Acton et al (2023) have not explicitly followed their eligibility criteria for their qualitative synthesis, (e.g., quantitative and non-dementia papers included) and therefor findings should be interpreted with caution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of everyday skills experienced by such persons has to be compensated for by a significant increase in the help provided by formal caregivers (Alzheimer's Association, 2022; Cleary & Doody, 2017a; Janicki et al, 2005; McCarron et al, 2005) This often results in a feeling of overload among formal caregivers as they are then left with relatively little time for other residents (the use of the term residents in these study means, persons who are living in the care facility for people with disabilities) (Gövert et al, 2016). Furthermore, as formal caregivers frequently report that they feel helpless and overwhelmed when dealing with dementia in people with intellectual disabilities (Acton et al, 2023; Grundwald et al, 2017), there may also be a drop in the quality of care provided (Herron et al, 2020; Rose & Rose, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Identifying dementia in people with intellectual disability is often reliant on those who provide care recognising the early signs and symptoms of cognitive decline (Dodd, 2014). However, carers often receive limited training or education about ageing in people with intellectual disability which can result in delays in identifying cognitive changes (Acton et al , 2023; Iacono et al , 2014). When cognitive changes are identified, the presence of behavioural distress can result in diagnostic delay, particularly in the early stages of dementia (Cleary and Doody, 2017).…”
Section: Introductionmentioning
confidence: 99%